The Mpa’a Geo Traditional Game Model in Preserving Bima Cultural Heritage in Physical Education Learning - Rabwan Satriawan; Salahudin; Ewan Irawan; Shutan Arie Shandi; Anas Ardiansyah (Universitas Tadulako, 2025)
The purpose of this study was to analyze the Mpa’a Geo game model in relation to the preservation of Bima culture at SMPN 3 Bima City. This research employed a qualitative approach with a descriptive design, utilizing both primary and secondary data sources. Data were analyzed through three stages: data reduction, data presentation, and conclusion drawing, conducted before and during fieldwork. The participants in this study were students from class 3A at SMPN 3 Bima City. The research instruments included observation sheets, interview guides, and documentation.The findings revealed that although numerous traditional games exist in the Bima region, their practice has gradually diminished over time. Traditional games offer various benefits, including: (1) fostering creativity, (2) serving as a therapeutic tool for children, (3) enhancing intellectual intelligence, (4) improving interpersonal and emotional intelligence, (5) developing logical reasoning, (6) strengthening kinesthetic abilities, (7) nurturing naturalistic intelligence, (8) enhancing intrapersonal intelligence, (9) improving musical intelligence, and (10) fostering spiritual growth. In contrast, modern games tend to reduce peer interaction and promote individualistic behavior among children. Therefore, it can be concluded that the Mpa’a Geo traditional game model contributes significantly to the preservation of Bima culture among students at SMPN 3 Bima City in physical education learning.